Optimal subsidy design for sports tourism under demand uncertainty: A multi-agent strategic interaction framework - Yuanyuan Yin (PLoS ONE, 2025)
This study develops a dynamic game model to analyze subsidy mechanisms for sports tourism integrated destination (STID), examining interactions between a core operator (major projects) and multiple supporting operators (ancillary services). It compares three scenarios: no subsidy, investment-based subsidies (core operator only), and visitor-driven subsidies (tied to tourist numbers). Results show investment-based subsidies increase core operator spending but not supporting operators’ investments, while boosting tourist numbers and supporting operators’ profits. Visitor-driven subsidies benefit all operators, increasing investments, profits and tourist volumes. When subsidy budgets are equal, visitor-driven subsidies yield better outcomes across all metrics if demand fluctuations remain stable. Demand shocks amplify both subsidy types’ effectiveness. Findings suggest visitor-driven subsidies better coordinate tourism ecosystems, with demand volatility enhancing subsidy impacts, while core and supporting operators require differentiated policy approaches due to asymmetric responses.